Impact of UEFA Champions League and UEFA Europa League on Financial Sustainability—Case Study of Two Small Football Portuguese Teams - Dantas, Florbela (2021)
Qualifying for European competitions allows football clubs to have access to the two most important football competitions played in Europe, UEFA Champions League and UEFA Europa League. Thereby, participation in these important competitions has both direct (participation prizes) and indirect (player transactions, television rights, box office, advertising, sponsorship) impacts on the sustainability of European football clubs’ accounts. The current competition model, which now includes more football teams, has become more attractive for small clubs. In this context, this research aims to analyze the impact of qualification for European competitions on the sustainability of a strong economic and financial structure of small clubs through a case study analysis of two small Portuguese clubs. The quantitative analysis is also supported by a comparative analysis, which was reinforced with nonparametric statistical analysis. The results show that the economic and financial impact on small clubs was not immediate, but was beneficial if it was managed efficiently. This research contributes to increasing knowledge of the decision-making agents of clubs that are participating for the first time in European competitions, or, if recurrent, are seeking answers and guidelines for the effective management of football teams